Social and economic gains of the elite sport - Scharapan, L. (2nd International Forum on Elite Sport. Barcelona, Centre d'Alt Rendiment (C.A.R.) de Catalunya, 11-13 September 2001, 2001)
Impact on the Australian economy of the staging of the 2000 Games. 1. The economic impact while hosting the Olympic Games. 2. The strategy of the Australian Tourist Commission to maximize the impact of the games